The Effect of Web Enhanced Course (WEC) and Web Centric Course (WCC) towards Student Learning Results on Reproduction System Concept - Ardiansyah, Ryan; Diella, Dea (Jurnal Penelitian dan Pembelajaran IPA, 2017)
Abstract Based on studies, many schools use e-learning web centric course (WCC) as an effort to improve student learning results. But in fact, WCC still has a lot of weaknesses. Therefore, this research was conducted for another e-learning which is based on web enhanced course (WEC) to overcome these WCC’s weaknesses. This study aimed to determine the effect of e-learning WCC and WEC for student learning results in grade XI in human reproduction system concept. The research methods used quasy experimental with non-equivalent group pretest posttest design and sample used 2 experimental groups that are WEC and WCC class in one of the high schools in Bandung with 30 students for each group which obtained by purposive sampling. Instruments used are multiple choice questions as the main data, questionnaires and interview guides as secondary data. Based on the result, average posttest for WEC is 81.90 and WCC is 69.96 with the hypothesis test result Zcount =3.89 in the retained area for Ztable =1.96. Based on these results, it can be conclude that there is learning effect of using e-learning WEC with WCC in students learning results in human reproductive system concept and using e-learning WEC can further increase student learning results when compared with WCC. Keywords: E-learning, Web Enhanced Course, Web Centric Course, Learning Results, Human Reproductive System